El espacio geográfico en el poema sollozo por Pedro Jara de Efraín Jara Idrovo - Pinta Delgado, Karla Valeria (2016)
The study The geographic space in the poem Sollozopor PedroJara by Efrain JaraIdrovo has as its main purpose to analyze the geographic space of this poem. To conduct this study, scientific,historical,deductive and inductive, analytic-synthetic, comparative and hermeneuticalmethods were used. These methods guidedthe systematicandlogical processof this study. The literaturesearchtechnique helped to find reliable information, the purpose of this search was todetermine the geographicalspace in the poem “Sollozopor Pedro Jara” itselementsand characteristics, whosegeographical spaceconsists ofthe Galapagos Islands.The space that Jaradesignedisa desolate,inert, and pure, space. Jara extractedelements of the naturallandscapethat help to achievea strongdegree ofpoetic, natural elementsas water,stone, rocks, seaweed, among others which are no longerelementsof the geographical spaceandare part ofa repertoire ofsuggestiveconnotations. The great landscapes of The Galapagos Islands have heavily influenced inthe poet's lifeby settingtheir perception andworldview, The islands constitute an intimate space to Jara.The scenario thatJara sets upis a scenario of purification, confrontation between theself and the world, death and life, the man and language,space and time,this iswhy,Sollozopor PedroJarahas becomea milestone in the Ecuadorianpoetry.